Florentino Ariza’s Loneliness Which Leads Into Self-Actualization In Love In The Time Of Cholera Movie - Andro, Nobertus Riko Juni (Jurnal Ilmiah Mahasiswa FIB, 2013)
Loneliness is the condition when one lack of social relationship, particularly love or intimate relationship. The effect of loneliness can be varied. It must be painful but for some people it is the chance to deeply know about them so that they can achieve self actualization.Love In The Time Of Cholera is the film dealing mostly with loneliness issues. It tells about a man who is loyal to wait for his lover , Fermina Daza. In waiting his lover he suffers from loneliness yet he wants to be a respected man in society so that Fermina Daza will regard his presence as an honourable man. This study employs qualitative research which uses Psychological Approach. The concepts used in exploring Love in the Time of Cholera Movie are Self-concept, Loneliness, and Existential Approach and combined with Self Actualization theory proposed by Abraham Maslow. The analysis of the movie is based on the script and picture in the movie. That is why; it is worth also to use mise en scene studies to strengthen the analysis. This research reveals how Florentino Ariza can achieve his self actualization within his loneliness. Since he cannot bear on the pain, he gets rid of his loneliness by having sex with 622 women. Yet, he still feels lonely since his love need cannot be fulfilled. Actually, his sex habit only satisfies his physiological need which is the basic need in Maslow’s hierarchy. Meanwhile, his loneliness which comes from his need of love will never be fulfilled if he cannot win Fermina’s heart again because he also builds his self-concept to be an eternal love for Fermina Daza. Keywords: loneliness, self actualization, love need